Additive Focus Adverbs in Canonical Word Orders. A Corpus-based Study of It. anche, Fr. aussi and E. also in Written News - De Cesare, Anna-Maria (Linguistik Online, 2015)
The goal of this paper is to offer a cross-linguistic analysis of the most commonly occurring additive focus adverbs used in Italian, French and English – namely anche, aussi and also – on the basis of a corpus of written texts. The corpus used in this paper consists of comparable online news in Italian, French and English amounting to approximately 750000 words. In line with previous findings, our results show that there are important quantitative and qualitative differences between It. anche, Fr. aussi and E. also. These items differ not only in their overall frequency of use but also in the specific syntactic configurations in which they occur when they associate with the Subject of a canonical sentence. These differences are partly enhanced by the fact that this paper concentrates on a non-prototypical configuration, i. e. on the cases in which the canonical Subject coincides with a new entity while the Predicate is maintained.